Tg(Afp-GFP) Expression Marks Primitive and Definitive Endoderm Lineages during Mouse Development - Kwon, Gloria S. (2006)
Alpha-fetoprotein (Afp) is the most abundant serum protein in the developing embryo. It is secreted by the visceral endoderm, its derivative yolk sac endoderm, fetal liver hepatocytes, and the developing gut epithelium. The abundance of this protein suggested that Afp gene regulatory elements might serve to effectively drive reporter gene expression in developing endodermal tissues. To this end, we generated transgenic mouse lines Tg(Afp-GFP) using an Afp promoter/enhancer to drive expression of green fluorescent protein (GFP). Bright GFP fluorescence allowed the visualization, in real time, of visceral endoderm, yolk sac endoderm, fetal liver hepatocytes, and the epithelium of the gut and pancreas. Comparison of the localization of green fluorescence with that of endogenous Afp transcripts and protein indicated that the regulatory elements used to generate these mouse lines directed transgene expression in what appeared to be all Afp-expressing cells of the embryo, but only in a subset of fetal liver cells. The bright GFP signal permitted flow cytometric analysis of fetal liver hepatocytes. These mice represent a valuable resource for live imaging as well as identification, quantitation and isolation of cells from the primitive and definitive endoderm lineages of the developing mouse embryo.